Depth-Dependence and Time-Dependence in Mechanical Behaviors of Articular Cartilage in Unconfined Compression Test under Constant Total Deformation - Natsuko HOSODA; Nobuo SAKAI; Yoshinori SAWAE; Teruo MURAKAMI (Journal of Biomechanical Science and Engineering, 2008)
Articular cartilage has high water content from 70 to 80% and biphasic property. The structures of the tissue are inhomogeneous and anisotropy. Consequently, cartilage tissue shows complicated viscoelastic behavior to mechanical stimuli because of depth-dependent and time-dependent interstitial fluid flux and stress-strain behaviors. Therefore it is necessary to consider not only the average tissue property but also the local one to explain mechanical and functional behaviors. The aim of this study is to consider the effect of elastic modulus distribution on the mechanical behavior of cartilage tissue using experiments with visualization and two-dimensional finite element method (FEM). In this study, we performed the compression test of the articular cartilage under the unconfined condition. First, on the basis of the distribution of Young's modulus in depth direction calculated from local strain at equilibrium in experiment, the stress and strain behaviors in articular cartilage were analyzed by biphasic theory. Immediately after loading, the FEM analysis for deformed profiles of the model with depth-dependent Young's modulus corresponded to actual profiles, while the model with average value for Young's modulus showed inadequate deformed profiles. However, the total load-carrying capacity estimated in FEM for the former model is about one order lower than the experimental one measured by a load cell. Therefore, we provided time-dependence to elastic property to understand the complicated viscoelastic behavior during stress relaxation. Thus, the deformed shape profiles of the model immediately after loading and the total load-carrying capacity could satisfactorily correspond to measured data by considering depth-dependent and time-dependent variation of elastic property.